Prekariat – nowe zjawisko na rynku pracy w Polsce - Cymbranowicz, Katarzyna (Annales. Etyka w Życiu Gospodarczym, 2016)
Studies of the scale of unemployment in Poland and in Europe conducted in recentyears lead to the conclusion that one of the largest and growing problems of themodern labour market is the unemployment rate among young people. An unfavourablephenomenon related to the problem that is increasingly appearing in publicdebate is the rising unemployment of graduates. Therefore, it is important to attemptto identify the phenomena in today's job market and one of them is the formation ofa new type of employee on the labour market, the member of the precarious class.The analysis aims to present the origins, nature and scale of the precariat phenomenonin Poland. The problem is described from the perspective of the labourmarket position of a selected social group, i.e. young people entering the labourmarket after finishing their education. The study attempted to identify factors thataffect this phenomenon and the characteristics confirming the sense of its separationon the labour market.